Schiller and Music - Longyear, R.M. (Chapel Hill The University of North Carolina Press, 1966)
In this first definitive study of Friedrich Schiller's relationship to music, R. M. Longyear discusses Schiller's personal, literary, and philosophical utilization of music as well as the influence of Schiller's works on composers from 1782 through the 1960s.
Andrew W. Mellon Foundation
National Endowment for the Humanities
English
Keywords: Literature: history & criticism; German Studies; Literature